Anti-Corruption Diagnostic for Argentina : An Overview of Three Reports and General Recommendations, Volume 1. Main Report - World Bank (Washington, DC, 2013)
In mid-1999, the World Bank initiated diagnostic studies of three topics relevant to improving public sector transparency in Argentina. The topics proposed for study--procurement, the detection and investigation of corrupt acts, and the role of public information--were seen to be critical to any Argentine Government program to combat corruption. The three resulting papers (to be attached as Annexes) are synthesized in the present overview which provides a number of specific recommendations for imprvements and a suggested course of action for the future. The research focused almost exclusively on the federal government, but holds lessons for the other levels (provincial and municipal) as well. The report describes the situation prior to the assumption of office by President Fernando de la Rua (December 10, 1999). President De la Rua has begun an anti-corruption program, which is addressing many of the problems identified here. This report does not and cannot assess these new efforts. The attached consultants' reports should be read with that understanding.